Energy characterization of an innovative non-equilibrium plasma ignition system based on the dielectric barrier discharge via pressure-rise calorimetry. (15th September 2021) - Ricci, F.; Discepoli, G.; Cruccolini, V.; Petrucci, L.; Papi, S.; Di Giuseppe, A.; Grimaldi, C.N.
Abstract: A dielectric barrier discharge igniter ( BDI ) ensures engine stable combustion at lean and/or diluted conditions by the generation of non-equilibrium low-temperature plasma ( LTP), strong promoter of the ignition, in a wide mixture volume. Beside this, a substantial amount of thermal energy is also released in the medium to enhance the chemical reactions of fuel oxidation. Therefore, the measurement of thermal energy is crucial to characterize the igniter capability to guarantee a robust combustion onset and it can be performed only in controlled environments. In this work, a Radio-Frequency BDI was tested via pressure-based calorimetry by evaluating the thermal energy released during the discharge in a controlled environment represented by a constant volume vessel. The corresponding thermal efficiency was evaluated as well. Pure nitrogen and air were exploited at engine-relevant pressure levels by varying the discharge features as its time duration and intensity (the latter by peak electrode voltage variation), to fully characterize the igniter behavior. Both media showed similar trends of absorbed and released energy but differences up to 50% were found for the latter. This trend was found to be linear, unexpectedly in contrast to the quadratic one showed by the LTP corona streamer-type igniter ( CSI ). Furthermore, the thermal energy dependence from pressure showed a change up to complete independence at a specific electrode value. To provide an explanation for such different behaviors, a comparative analysis between the diverse discharges of the two igniters was carried out. Moreover, by varying voltage and duration, the device was found to be able to release up to 60 mJ in the tested point with very low dispersion, essential to guarantee stable combustion ignition at challenging operating conditions for next-generation internal combustion engines.